A incidência do ISSQN sobre os serviços prestados por respondente / interino dos cartorários extrajudiciais - Silva, Cleusinéia Matos da (2015)
This research has the main objective of establishing the illegality of charging ISSQN over registry services provided by respondent / interim, as this person is an agent of the State. This research analyzes the ISSQN and the service concept, its definition and competence, taxable event, the basis of calculation, rate, taxpayer, place of performance and the launch. Points incidence of ISSQN in registry services considering the notarial records and public activity, the professionals who provide service requirements for entry, civil and criminal liability, incompatibilities and impediments, disciplinary offenses and penalties. This research examines the jurisprudential positions regarding the levying of ISSQN on notarial registry services and public records, in light of ADI 3089 / DF and incidence of wage cap and amputation of the administrative autonomy of the respondent / caretaker, made by means of an injunction 29039 and Resolution 80 of the National Council of Justice,without forgetting the basic principle for elucidation of the research that is the principle of reciprocal immunity.